2020
DOI: 10.1016/j.ctro.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of normal lung density changes with dose after stereotactic body radiotherapy (SBRT) for early stage lung cancer

Abstract: Background and Purpose: To investigate the correlation between normal lung CT density changes with dose accuracy and outcome after stereotactic body radiation therapy (SBRT) for patients with early stage non-small-cell lung cancer (NSCLC). Materials and Methods: Thirty-one patients (with a total of 33 lesions) with non-small cell lung cancer were selected out of 270 patients treated with SBRT at a single institution between 2003 and 2009. Out of these 31 patients, 10 patients had developed radiation pneumoniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…As Feghali et al. studies ( 5 ), ΔHu in peritumoral region was positively correlated with RP grade. Phernambucq et al.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…As Feghali et al. studies ( 5 ), ΔHu in peritumoral region was positively correlated with RP grade. Phernambucq et al.…”
Section: Discussionsupporting
confidence: 52%
“…The density change in this threshold range is related to the occurrence of RP. As Feghali et al studies (5), DHu in peritumoral region was positively correlated with RP grade. Phernambucq et al (7) found that the threshold dose of lung dose density change was 30 Gy, and there was only slight density change at low dose level.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations